2019
DOI: 10.1029/2018gc007663
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Evidence for a Mantle Transition Zone Origin of the Wudalianchi and Halaha Volcanoes in Northeast China

Abstract: There exists much debate about origins of Cretaceous to present volcanism in northeast (NE) China. Here we present high‐resolution seismic images of the upper mantle beneath NE China obtained by inverting P wave traveltime data recorded by two dense linear arrays. The inclusion of the new data set has greatly improved sampling of the upper mantle beneath the study region, providing tight constraints on the seismic structure under the intraplate Wudalianchi and Halaha volcanoes. Local‐scale low P wave velocity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 76 publications
5
53
0
Order By: Relevance
“…Upwelling from the mantle transition zone and lower upper mantle or the deep mantle has also been proposed to have been active for >15 Ma, and thus for the entire younger Cenozoic (i.e., Quaternary and Neogene; Kimura et al, ; Kuritani et al, , ; Tang et al, ; Wang et al, ; Xu et al, ). The present‐day mantle above the stagnant plate, the so‐called big mantle wedge ‐ and also the upper mantle beyond it to the west and the lower mantle ‐ shows large‐scale dV S and dV P anomalies of mostly ≤ ±3% and ±2% (Figure b; Chen et al, ; Huang & Zhao, ; Kimura et al, ; Tang et al, ; Wei et al, ). The upper mantle seismic anomalies compare in intensity to those of, for example, the Yellowstone mantle plume ( dV S =−4 to +2%, dV P =−2 to +1%; Waite et al, 2006), but they are small compared to velocity variations in volcanic arc systems (with velocity anomalies of commonly up to ±10%; Widiyantoro et al, ).…”
Section: Background and Geological Settingmentioning
confidence: 99%
See 4 more Smart Citations
“…Upwelling from the mantle transition zone and lower upper mantle or the deep mantle has also been proposed to have been active for >15 Ma, and thus for the entire younger Cenozoic (i.e., Quaternary and Neogene; Kimura et al, ; Kuritani et al, , ; Tang et al, ; Wang et al, ; Xu et al, ). The present‐day mantle above the stagnant plate, the so‐called big mantle wedge ‐ and also the upper mantle beyond it to the west and the lower mantle ‐ shows large‐scale dV S and dV P anomalies of mostly ≤ ±3% and ±2% (Figure b; Chen et al, ; Huang & Zhao, ; Kimura et al, ; Tang et al, ; Wei et al, ). The upper mantle seismic anomalies compare in intensity to those of, for example, the Yellowstone mantle plume ( dV S =−4 to +2%, dV P =−2 to +1%; Waite et al, 2006), but they are small compared to velocity variations in volcanic arc systems (with velocity anomalies of commonly up to ±10%; Widiyantoro et al, ).…”
Section: Background and Geological Settingmentioning
confidence: 99%
“…Several of the low‐velocity anomalies beneath Eastern China unquestionably extend from the top of the mantle transition zone to the surface, while it remains debated if they also locally connect through slab gaps to the lower mantle (Chen et al, ; Tang et al, ; Wei et al, ), or if they connect to a deep mantle plume (i.e., the Datong mantle plume; Kimura et al, ). The large scale of the seismic anomalies in the upper mantle (Figure ) and vertical mantle flow velocities (≤4 cm/year; Cheng et al, ) highlight that the presently observed anomalies must have developed >10 Ma ago.…”
Section: Background and Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations